2003
DOI: 10.1055/s-2003-37307
|View full text |Cite
|
Sign up to set email alerts
|

Selektive ventrale Derotationsspondylodese bei idiopathischen Thorakalskoliosen: eine prospektive Studie

Abstract: Selective anterior correction and fusion in idiopathic thoracic scoliosis enables a satisfactory correction of both primary and lumbar secondary curves. The advantage of selective anterior correction and fusion of thoracic scoliosis is the short fusion length, better derotation and satisfactory correction of the secondary lumbar curve. The disadvantages of single threaded rod techniques in terms of lack of primary stability and a kyphogenic effect have been eliminated by the development of a primary stable, sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…A significant correction loss of an average of 2°was proved between immediate postoperative measurement and follow-up; a long-term correction of 51% was consequently achieved. Bullmann et al [8] published similar values in their prospective study comprising 64 patients with idiopathic thoracic scoliosis.…”
Section: Frontal Plane Correctionmentioning
confidence: 69%
See 1 more Smart Citation
“…A significant correction loss of an average of 2°was proved between immediate postoperative measurement and follow-up; a long-term correction of 51% was consequently achieved. Bullmann et al [8] published similar values in their prospective study comprising 64 patients with idiopathic thoracic scoliosis.…”
Section: Frontal Plane Correctionmentioning
confidence: 69%
“…This instrumentation was developed to preserve the efficiency of ventral derotation spondylodesis when a relatively short fusion length corrected scoliosis on the one hand and on the other hand to complete it in such a way that a primary stable instrumentation significantly reduced the rate of breakages and allowed brace-free postoperative care. In addition, kyphogenic effect was to be decreased [8,14,16]. In a prospective study comprising 45 patients with idiopathic scoliosis, Bullmann et al were able to show that a good correction of the scoliotic major curve and the apical rotation were achieved equally by using the Halm-Zielke instrumentation.…”
Section: Introductionmentioning
confidence: 99%
“…Posterior instrumentation and fusion represent the gold standard in the treatment of idiopathic thoracic scoliosis. However, there are reports in the literature indicating favourable results of anterior instrumentation and fusion in terms of a better three-dimensional curve correction and a shorter fusion length [1,3,14,22,25,30]. In this prospective study, 23 consecutive patients were treated with an anterior dual rod instrumentation and fusion.…”
Section: Discussionmentioning
confidence: 98%
“…The average fusion length was 6.1 segments with an average frontal curve correction of 58% and a loss of correction of 1.3°within fusion levels. In publications on standard open single rod instrumentation in thoracic scoliosis the reported primary curve correction ranges from 43 to 58% with a loss of correction of 1 to 5°and a pseudarthrosis rate of up to 6% [3,7,20,22,30]. Betz et al [1] reported on a loss of correction of more than 10°in 23% of their patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation